Structural Phase State and Thermal Cyclic Stability of the Thermal Barrier Zr–Si–O Coatings Deposited on a Copper Substrate by the Microplasma Method; Protection of Metals and Physical Chemistry of Surfaces; Vol. 55, iss. 4 - Dorofeeva T. I. Tamara Ivanovna; Gubaydullina T. Tatjyana; Gricenko (Gritsenko) B. P. Boris Petrovich; Sergeev V. P. Viktor Petrovich (2019, 2019)
Title screen